Phonon spectra and vibrational heat capacity of quasi-one-dimensional structures formed by rare gas atoms on the surface of carbon nanotube bundles - Manzhelii, E.V.; Feodosyev, S.B.; Gospodarev, I.A. (Физика низких температур, 2019)
The features of phonon spectra and their effect on the vibrational heat capacity of linear chains of inert gas atoms adsorbed onto a substrate, which is the surface of nanotubes bound to a nanobundle. The influence of the substrate results both in a shift of the lower limit of the chain spectrum from zero, and in mechanical stress in the chain (its extension or compression) also. It is shown that in the case of a compressed chain, the non-central interaction between atoms is negative (repulsive), it results in a shift of the lower boundary of the spectrum of transverse vibrations to low frequencies and to a shortening of the part of the specific heat temperature dependence in which this dependence is close to exponential. Heterogeneity of the nanobundle structure can cause a change in the distances between atoms of the chain. It is shown both and analytically and numerically, that as a result of it, discrete levels with frequencies both above and below the quasi-continuous spectrum band can appear in the phonon spectrum of the chain. The discrete levels with frequencies below the quasi-continuous spectrum band lead to a further shortening of the temperature interval at which the temperature dependence of the specific heat is close to the exponential one.